Theoretical study of porous surfaces derived from graphene and boron nitride - Fabris, G. S. L. [UNESP]; Marana, N. L. [UNESP]; Longo, E.; Sambrano, J. R. [UNESP] (Elsevier B.V., 2018)
Porous graphene (PG), graphenylene (GP), inorganic graphenylene (IGP-BN), and porous boron nitride (PBN) single-layer have been studied via periodic density functional theory with a modified B3LYP functional and an all-electron Gaussian basis set. The structural, elastic, electronic, vibrational, and topological properties of the surfaces were investigated. The analysis showed that all porous structures had a nonzero band gap, and only PG exhibited a non-planar shape. All porous structures seem to be more susceptible to longitudinal deformation than their pristine counterparts, and GP exhibits a higher strength than graphene in the transversal direction. In addition, the electron densities of GP and IGP-BN are localized closer to the atoms, in contrast with PG and PBN, whose charge density is shifted towards the pore center; this property could find application in various fields, such as gas adsorption.
Keywords: Porous graphene; Graphenylene; DFT; Inorganic graphenylene; Porous boron nitride